Sistem Pakar Berbasis Web Diagnosa Penyakit Gigi dan Mulut di Klinik Sehati - Rika Nurhayati; Satria Nusantara Achmad (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2022)
The lack of knowledge of dental and oral health and the limited number of dentists causes low public awareness of dental and oral health. This condition makes some people put aside efforts to prevent and treat dental and oral diseases. Therefore, this study has created an expert system for early diagnosis of dental and oral diseases, so that it can help the public to find out about the dental and oral diseases they are suffering from and overcome the problem of scarcity of dental and oral experts. As for designing the decision support system are use the Expert System method for evaluating criteria and sub-criteria, with the Personal Home Page (PHP) programming language, MySQL as a database server, APPSERV as a web server. The results of this information system design are web applications. to input data on the symptoms of the disease suffered by the patient, then carry out the process of selecting the symptoms of the disease and produce a diagnosis result in the form of disease and healing solutions.